Participant Perspectives and Experiences Entering an Intensively Monitored Antiretroviral Pause: Results from the AIDS Clinical Trials Group A5345 Biomarker Study - Diepstra, Karen L. (AIDS Res Hum Retroviruses, 2021)
The AIDS Clinical Trials Group (ACTG) A5345 study included an intensively monitored antiretroviral pause (IMAP), during which a cohort of participants temporarily stopped antiretroviral treatment during chronic HIV infection. We surveyed participant perceptions and understanding of A5345 using a cross-sectional sociobehavioral questionnaire. Participants completed the baseline questionnaire either before or after initiating the study's IMAP. Questionnaire responses were linked to existing demographic data. Quantitative responses were analyzed overall and stratified by IMAP status. Open-ended responses were analyzed using conventional content analysis. Thirty-two participants completed the baseline sociobehavioral questionnaire. Half (n = 16) completed it before (i.e., pre-IMAP initiation group) and half (n = 16) after IMAP initiation (i.e., post-IMAP initiation group). Eight pre-IMAP initiation respondents (50%) and 11 post-IMAP respondents (69%) responded “yes” when asked if they perceived any direct benefits from participating in A5345. Perceived societal-level benefits included furthering HIV cure-related research and helping the HIV community. Perceived personal-level benefits included the opportunity to learn about the body's response to IMAP and financial compensation. The majority of respondents—13 from each group (81% of each)—reported risks from participation, for example, viral load becoming detectable. A5345 participants perceived both societal- and personal-level benefits of study participation. While the majority of survey respondents perceived participatory risks, nearly one in five did not. Key messages pertaining to study-related risks and benefits may need to be clarified or reiterated periodically throughout follow-up in HIV cure-related studies with IMAPs. Clinical Trail Registration Number: NCT03001128.